Ergometrine stability in postpartum haemorrhage kits: Does temperature and light matter? - Donnan, F.; Senarathna, Ganga; Ware, B.; Rawlins, M.D.M.; Dontham, C.; Chuang, Victor; Batty, Kevin (WILEY, 2020)
Background: Postpartum haemorrhage (PPH) kits containing uterotonics are used on obstetric units for the timely management of PPH. Visible discolouration of ergometrine and ergometrine-oxytocin injections was observed in PPH kits stored in medical refrigerators on the obstetric unit at our hospital.